Labor: An unexploited opportunity for social integration of disabled persons - Gąciarz, Barbara (Journal of Public Governance, 2011)
The author of the paper analyzes the model of social policy toward the disabled in Poland and reviews key barriers for its effective implementation. She discusses constraints related to institutional, political and social capacities. Based on the results of sociological research conducted in 2001-2009, the problem of economic activity of the disabled is analyzed and some recommendations are presented related to changes in the paradigm of the policy toward the disabled: from a compensation model to an integration-oriented model. The low rate of employment of disabled people in Poland is identified as one of the principal causes of their social exclusion. The profound change in this area is recommended as an action that might lead to a sustainable improvement of the socio-economic situation of the disabled in Poland. Some recommendations for this change are formulated based on the concept of good governance.